Dwarfism in beef cattle - Smith, W.H.; Holland, L.A. (Kansas Agricultural Experiment Station, 2012)
During recent years there have been several scientific and numerous breeders' reports on dwarfism in the Angus, Hereford, and Shorthorn breeds of beef cattle. These have described what appear to be several different kinds of dwarfism, only two of which are apparently associated with recognizable types of cattle. Many of the scientific publications have discussed the mode of inheritance as well as the description of the kind of dwarfism considered. The general problem is complex and research pertaining to most phases of it is as yet in the preliminary stages; however, there are some important facts known at this time which should be understood by breeders who are attempting remedial measures to suppress incidence of dwarfism in breeding herds.
Keywords: Beef; Dwarfism